2003
DOI: 10.1038/nn1023
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin improves long-lasting spatial memory during motherhood through MAP kinase cascade

Abstract: Oxytocin is an essential hormone for mammalian labor and lactation. Here, we show a new function of oxytocin in causing plastic changes in hippocampal synapses during motherhood. In oxytocin-perfused hippocampal slices, one-train tetanus stimulation induced long-lasting, long-term potentiation (L-LTP) and phosphorylation of cyclic AMP-responsive element binding protein (CREB), and MAP kinase inhibitors blocked these inductions. An increase in CREB phosphorylation and L-LTP induced by one-train tetanus were obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
249
1
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 326 publications
(278 citation statements)
references
References 37 publications
12
249
1
3
Order By: Relevance
“…Indeed, OT has been shown to increase spike output [89][90][91] and facilitate synaptic long-term potentiation [92][93][94] and our data suggest an intrinsic mechanism that may underlie shifts in synaptic efficacy and excitatory/inhibitory balance found in brain regions where OT is critical for myriad social behaviors 67,74,90,95 . Intrinsic properties are shaped by ion channels.…”
Section: Discussionmentioning
confidence: 54%
“…Indeed, OT has been shown to increase spike output [89][90][91] and facilitate synaptic long-term potentiation [92][93][94] and our data suggest an intrinsic mechanism that may underlie shifts in synaptic efficacy and excitatory/inhibitory balance found in brain regions where OT is critical for myriad social behaviors 67,74,90,95 . Intrinsic properties are shaped by ion channels.…”
Section: Discussionmentioning
confidence: 54%
“…Further, the MAPK pathway has been demonstrated to be integral to progestins 0 functional effects; blocking MAPK attenuates the intracellular actions of P 4 or membrane actions of 3a,5a-THP to enhance sexual behavior among rats (González-Flores et al 2004, Acosta-Martínez et al 2006. Tomizawa et al (2003) have found that MAPK inhibition also attenuates LTP in multiparous mouse hippocampal slices. These data suggest that signal transduction factors are important in steroid actions and may, in part, underlie some functional cognitive performance changes associated with endogenous E 2 and progestin elevations.…”
Section: Discussionmentioning
confidence: 98%
“…The resulting endocrine milieu, as well as limbic morphology and function, are altered following pregnancy, parturition, and/or pup rearing (Featherstone et al 2000, Tomizawa et al 2003, Pawluski & Galea 2006. First, oxytocin associated with motherhood enhances longterm potentiation (LTP) of hippocampal tissue slices in culture and central infusions of oxytocin enhance longterm spatial memory in virgin mice (Tomizawa et al 2003). Second, hippocampal spinal density is increased in pregnant compared with non-pregnant rats and is also altered by postpartum mothering (Kinsley et al 2006, Pawluski & Galea 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Although we may infer that E 2 and/or progestins during pregnancy influence cognitive performance, 1 st trimester rats did not have enhanced performance in this task, which may be due to effects of the many pregnancy hormones that are changing at this time. Prolactin, oxytocin, and glucocorticoids are all elevated during pregnancy in rats, are known to influence brain structures, and may be involved in the modulation of spatial cognition (Grattan, 2002;Oitzl et al, 1998;Roozendaal et al, 1996;Shingo et al, 2003;Tomizawa et al, 2003). For that reason, it is essential to examine effects on cognitive performance of both endogenous variations in hormones and effects of systemic hormone-replacement.…”
Section: Discussionmentioning
confidence: 99%